Low Heart Rate Variability Predicts Stroke and Other Complications in the First Six Postoperative Months After a Hip Fracture Operation - Ernst, Gernot; Watne, Leiv Otto; Frihagen, Frede; Wyller, Torgeier Bruun; Dominik, Andreas; Rostrup, Morten (Frontiers in Cardiovascular Medicine, 2021)
Background: 1-year mortality after hip fractures is underestimated and is reported as 25 %. An improved risk stratifying could contribute to a better follow up of these patients. Heart Rate Variability (HRV) is an easy point-of-care investigation and is been used in cardiology, endocrinology, and perioperative care. This observational study intended to explore relevant associations between HRV parameters and 6-months mortality and morbidity after a hip fracture. Methods: 165 patients admitted to two hospitals were included, and short-time HRV measurements (5 minutes, and 10 minutes at the two hospitals, respectively) were obtained. Mortality data were gathered by means of the Norwegian central address register. Patients, close relatives of patients, and in some cases their general physicians or nursery home physicians were interviewed six months postoperatively regarding the incidence of pneumonia, cardiac events, or stroke. Results: 157 (95.2%) patients were followed up after six months post-surgery. 21 (13%) died during this period. Twenty patients (13%) developed pneumonia, eight (5 %) stroke and four (2%) myocardial infarction. No HRV parameter was associated with six-month general mortality. However, patients who developed stroke had significantly lower High Frequency Power (HF, p< 0.001) and lower Very Low Frequency Power (VLF, p=0.003) at inclusion compared to patients without complications. Patients who developed pneumonia had at the inclusion lower root mean square of successive differences (RMSSD, p = 0.044). Patients with a history of coronary heart disease (n = 41) showed a mortality of 7%. Mortality in this group was associated with standard deviation of beat-to-beat intervals (SDNN, p = 0.006), Total Power (TP, p = 0.009), HF (p = 0.026), and Low Frequency Power (LF, p = 0.012). Beta-blocker intake was associated with lower heart rate, but not with differences in HRV parameters. Conclusion: In this exploratory study, we present for the first-time significant associations between different preoperative HRV parameters and stroke, myocardial infarction, and pneumonia during a 6-month period after hip fracture. HRV might be a simple and effective tool to identify patients at risk that would warrant better follow-up.